Are We Approaching a Change in Paradigm in PET/CT Imaging of Solid Gastrointestinal (or Digestive) Tract Tumors With the Clinical Application of FAPI Imaging?. (8th April 2023) - Delgado Bolton, Roberto C.; Calapaquí Terán, Adriana K.; Herrmann, Ken; Fanti, Stefano; Giammarile, Francesco
Abstract: Studies with [ 68 Ga]Ga-labeled or [ 18 F]F-labeled fibroblast activation protein inhibitor compounds have demonstrated favorable characteristics for PET/CT imaging, making them especially interesting for digestive tumors. In this review, the recent evidence in this field and its potential clinical applications are discussed.